2009
DOI: 10.5694/j.1326-5377.2009.tb02471.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and their relationship with chronic diseases: a review of the epidemiology, risk and treatment evidence

Abstract: Objective: To review the evidence for an association between depression and anxiety and the National Health Priority Area conditions — heart disease, stroke, diabetes mellitus, asthma, cancer, arthritis and osteoporosis — and for the effectiveness of treatments for depression and anxiety in these settings. Data sources: Systematic literature search of systematic reviews, meta‐analyses and evidence‐based clinical practice guidelines published between 1995 and 2007, inclusive. Data extraction: Each review was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
357
3
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(417 citation statements)
references
References 96 publications
27
357
3
11
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 4 Although some reviews on the effects of Qigong and Tai Chi have also been conducted, 9-13 they were not conclusive because they were either not quantitative reviews or had several limitations.…”
Section: Page 4 Of 47mentioning
confidence: 99%
See 1 more Smart Citation
“…A c c e p t e d M a n u s c r i p t 4 Although some reviews on the effects of Qigong and Tai Chi have also been conducted, 9-13 they were not conclusive because they were either not quantitative reviews or had several limitations.…”
Section: Page 4 Of 47mentioning
confidence: 99%
“…1 Depression is associated with a range of physical illnesses, including stroke, diabetes, cancer, arthritis, osteoporosis, and obesity, 3,4 and the onset of depression incrementally worsens the latter health problems. [5][6][7] Interventions to tackle this problem are therefore important and previous studies have indicated an important role for physical activity in the management of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Depression seriously affects the way someone eats, sleeps, and works [4] and concomitantly disrupts social relationships, economic status, and sense of self-esteem. Moreover, the coexistence of depression and chronic diseases is a common finding, and its role in initiation and/or aggravation of these diseases is highlighted in research literature [5][6][7]. Serum 25 hydroxyvitamin D (25(OH)D) deficiency or insufficiency is a global health problem and estimated to affect one billion people worldwide [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of poor psychological well-being in PCOS is important to prompt intervention and improve self-efficacy through effective lifestyle change to improve clinical outcomes in this chronic and common condition. The clinical relevance of depression in infertility may be of consequence to women's ability to make lifestyle and behavior changes through self-efficacy also, as has been observed in other chronic conditions (28). Given that past research has found that infertile women (all causes) have higher rates of depression than fertile women (20), infertility may add additionally to depression in PCOS, and this finding requires further exploration.…”
mentioning
confidence: 95%